Impact of an Opt-In eConsult Program on Primary Care Demand for Specialty Visits: Stepped-Wedge Cluster Randomized Implementation Study - Rikin, Sharon (J Gen Intern Med, 2020)
BACKGROUND: eConsult programs have been instituted to increase access to specialty expertise. Opt-in choice eConsult programs maintain primary care physician (PCP) autonomy to decide whether to utilize eConsults versus traditional specialty referrals, but little is known about how this intervention may impact PCP eConsult adoption and traditional referral demand. OBJECTIVE: We assessed the feasibility of implementing an opt-in choice eConsult program and examined whether this intervention reduces demand for in-person visits for primary care patients requiring specialty expertise. DESIGN: Stepped-wedge, cluster randomized trial conducted from July 2018 to June 2019. PARTICIPANTS: Sixteen primary care practices in a large, urban academic health care system. INTERVENTION: Our intervention was an opt-in choice eConsult available in addition to traditional specialty referral; our implementation strategy included in-person training, audit and feedback, and incentive payments. MAIN MEASURES: Our implementation outcome measure was the eConsult rate: weekly proportion of eConsults per PCP visit at each site. Our intervention outcome measure was traditional referral rate: weekly proportion of referrals per PCP visit at each site. We also assessed PCP experiences with questionnaires. KEY RESULTS: Of 305,915 in-person PCP visits, there were 31,510 traditional referrals to specialties participating in the eConsult program, and 679 eConsults. All but one primary care site utilized the opt-in choice eConsult program, with a weekly rate of 0.05 eConsults per 100 PCP visits by the end of the study period. The weekly rate of traditional referrals was 11 per 100 PCP visits at the end of the study period; this represents a significant increase in traditional referral rate after implementation of eConsults. PCPs were generally satisfied with the eConsult program and valued prompt provider-to-provider communication. CONCLUSIONS: Implementation of an opt-in choice eConsult program resulted in widespread PCP adoption; however, this did not decrease the demand for traditional referrals. Future studies should evaluate different strategies to incentivize and increase eConsult utilization while maintaining PCP choice.